1st National Seminar: Biotechnology, Health & Agro-Environment. NSBHAE 2022 - Department of biology (University of Eloued جامعة الوادي, 2022)
The application of innovative technology in the health, agronomy and ecology sector requires describing the heritage, the constraints and the challenges linked to its application. There are intersections of different types between these sectors; from the point of view of the use of bioresources in the food and medical industries which may present an environmental pollutant. Indeed; The current observation of our environment and the elements that constitute it (air, water, earth ...), invite us to reflect on its future and especially on the natural capital that we will bequeath to future generations. Besides, various living beings contain in addition primary or secondary metabolism substances (Bioactive Substances), the presence of these substances makes these organisms of therapeutic, agricultural or industrial value. Meetings aimed at describing the application of biotechnology in the fields already mentioned are necessary. Thus, we are forced to develop bio-products with a low or neglected polluting effect.
. 1st National Seminar: Biotechnology, Health & Agro-Environment. NSBHAE 2022. 14 & 15 March 2022 Department of biology. University of ElOued
Keywords: Biotechnology, Health , Agro-Environment, Agri-Food Biotechnology, Biotechnology and Health, Biotechnology and Environment